1985
DOI: 10.1007/bf00436969
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of the alkaloid lycorine on rho +, mit +, rho -, and rho° strains of Saccharomyces cerevisiae

Abstract: Due to an error in the preparation of Table 2, the figures in part B) and part C) are not in the right position. The corrected Table 2 now reads as follows:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Interestingly, petite mutations are associated with a decreased susceptibility of yeasts to various chemicals, such as tannic acid or the alkaloid lycorine (7,37). Likewise, Gyurko et al (11) recently demonstrated that respiration-deficient mutants of C. albicans were resistant to histatin 5, a small cationic salivary antimicrobial peptide, mitochondrial ATP synthesis being required for effective killing activity of this salivary peptide.…”
Section: Influence Of Respiratory Chain Inhibitors (I) Oxygen Consummentioning
confidence: 99%
“…Interestingly, petite mutations are associated with a decreased susceptibility of yeasts to various chemicals, such as tannic acid or the alkaloid lycorine (7,37). Likewise, Gyurko et al (11) recently demonstrated that respiration-deficient mutants of C. albicans were resistant to histatin 5, a small cationic salivary antimicrobial peptide, mitochondrial ATP synthesis being required for effective killing activity of this salivary peptide.…”
Section: Influence Of Respiratory Chain Inhibitors (I) Oxygen Consummentioning
confidence: 99%
“…In previous papers we have demonstrated that lycorine inhibits growth of rho + , rho À and mit À strains, whereas rho 0 strains (devoid of mtDNA) of S. cerevisiae are resistant to high concentrations of the drug (Del Giudice et al, 1984;Massardo et al, 2000). In a search for new genes whose expression is RTGdependent in mitochondria to nucleus signaling we have analyzed the growth of isogenic rho 0 Drtg strains with different doses of lycorine.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, neither respiration nor mitochondrial protein synthesis are responsible for the differential effect of lycorine (Del Giudice et al, 1984).…”
Section: Effect Of Lycorine On Macromolecular Synthesesmentioning
confidence: 88%
See 1 more Smart Citation
“…Wild-type rho + cells, neutral rho -cells, and moderately suppressive rho -cells are all sensitive to the lycorine; rho 0 cells, however, are resistant to high concentration of the drug (Del Giudice et al 1984). Most hyper-suppressive rho -strains show an intermediate resistance to lycorine (Massardo et al 1990).…”
Section: Introductionmentioning
confidence: 98%